PENERAPAN MODEL PEMBELAJARAN PROBLEM BASIC LEARNING (PBL) UNTUK MENINGKATKAN HASIL BELAJAR BAHASA INDONESIA KELAS III SDN 064971 MEDAN TEMBUNG - Lastiur Manurung; Indah Pratiwi; Atti Siregar (STKIP Subang, 2024)
Thematic learning outcomes of Indonesian language learning outcomes are low because the learning that is done is still conventional, which causes students' involvement in learning is still low.conventional, which causes student involvement in learning is still minimal. This study aims to analyze the effect of problem-based learning model on learning model on the learning outcomes of Indonesian language content in grade III elementary school.grade III elementary school students. This research is a class action research research which was conducted in two cycles. Each cycle consists of four stages: planning, implementation, observation, and reflection. The subject of the researchwere third grade students totaling 13 students, consisting of 6 female students and 7 male students.. Data collection was carried out by the test method, in the form of ordinary multiple choice test. The collected data were analyzed using descriptive descriptive statistics. The results showed that the average learning outcomes of Indonesian language content in cycle I was 63.93 with a low category, so the research was continued to cycle II. with a low category, so the research continued to cycle II. In cycle II, the average learning outcomes of thematic Indonesian language lessons increased to 79.82 with a high category. Based on the research results,it can be concluded that the problem-based learning model is effective in improving students' Indonesian language thematic learning outcomes.